2011
DOI: 10.7127/rbai.v5n300055
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação agronômica de cultivares de soja sob irrigação no semiárido mineiro

Abstract: The treatments consisted of eight soybean cultivars, M-SOY 9350, M-SOY 8787 RR, M-SOY 8352 RR, CD 219 RR, P98Y51, P98Y70, P99R01, P99R91. We adopted the randomized block design with four replications. Each plot consisted of four rows of 10 m. The center two line, less 50 cm from the ends, was the usable area. The used culture installation and cultural practices were the standard for soybean cultivation. The conventional sprinkler was used in the experiment. The height of first pod insertion and plant, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Constitui-se em um importante polo de agricultura irrigada no Brasil, sendo que, cerca de 13,5 mil hectares da área destinada a cultura, utiliza equipamentos de irrigação do tipo pivô central (G1, 2016), que são acionados para suprir a deficiência hídrica em fases críticas da cultura, como no florescimento (AQUINO et al, 2011), possibilitando até três safras anuais. Entretanto, falta ainda adequação de tecnologias, como melhor posicionamento dos materiais genéticos quanto à adaptação às condições edafoclimáticas da referida região.…”
Section: Introductionunclassified
“…Constitui-se em um importante polo de agricultura irrigada no Brasil, sendo que, cerca de 13,5 mil hectares da área destinada a cultura, utiliza equipamentos de irrigação do tipo pivô central (G1, 2016), que são acionados para suprir a deficiência hídrica em fases críticas da cultura, como no florescimento (AQUINO et al, 2011), possibilitando até três safras anuais. Entretanto, falta ainda adequação de tecnologias, como melhor posicionamento dos materiais genéticos quanto à adaptação às condições edafoclimáticas da referida região.…”
Section: Introductionunclassified
“…In a study by Rocha et al (2012) comparing soybean cultivars, it was observed that grain mass varies among cultivars. Likewise, Aquino et al (2011) observed an average difference among eight cultivars tested for grain mass, and the number of pods per plant may vary according to the cultivar.…”
Section: Resultsmentioning
confidence: 89%
“…Nesta pesquisa, identificou-se uma clara predominância de estudantes do sexo feminino, o que já se verificava em outros estudos realizados (CABRITA et al, 2001;CORREIA et al, 2010;SOARES, 2017;LUNA et al, 2018;TAM et al, 2018), entretanto, não foi identificada diferença estatística significativa quanto ao uso de psicofármacos entre os sexos, diferentemente do observado em outras pesquisas (SEEMAN, 1997;AQUINO;BARROS;SILVA, 2010).…”
Section: Discussionunclassified